Systematic Literature Review: Kuliner Tradisional Sumatera Selatan sebagai Cerminan Nilai Budaya Lokal - Azizah Nurul Aini; Desi Ratna Sari; Wasino; Argitha Aricindy (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
South Sumatra's traditional culinary delights are a reflection of local cultural values ​​that contain historical, social meaning and the wisdom of the local community. Typical foods such as pempek, gulo puan, and srikaya cake not only function as consumption necessities, but also represent cultural identity passed down from generation to generation. However, in the midst of modernization and globalization, the existence of traditional culinary delights is facing threats in the form of shifts in public interest, minimal documentation, and a lack of systematic promotional strategies, which have the potential to erode long-established local cultural values. As an effort to solve the problem, this study comprehensively examines the role of traditional culinary delights as symbols of local cultural values ​​as well as their potential in supporting the development of gastronomic tourism in South Sumatra. The method used was Systematic Literature Review (SLR) with the PRISMA 2020 protocol. The selection process was carried out systematically on relevant literature, and a total of 9 scientific articles published in the 2019–2025 period met the inclusion criteria for further analysis. The results of the study show that traditional South Sumatran culinary delights have strong cultural values, including the values ​​of togetherness, tradition and creativity of the local community. Apart from that, it was found that culinary development requires product innovation, use of digital technology, and effective promotional strategies to remain relevant in the modern era. This study concludes that South Sumatra's traditional culinary delights not only act as cultural heritage that needs to be preserved, but are also strategic assets in strengthening regional identity and increasing economic potential through the gastronomic tourism sector